TEMPORAL AND SPATIAL VARIATIONS OF HEAVY METALS IN SHELLFISH IN BANTEN BAY: VARIASI TEMPORAL DAN SPASIAL LOGAM BERAT PADA KERANG DAN KEPITING DI TELUK BANTEN - Annisa Dinulislam; Tsalista Salsabilla; Tresna Melinda; Dwi Indah Sulistyowati; Ertika Noviani; Dita Fatryani; Nadya Febrianessa; Hanifah Nedya; Sulistiono Sulistiono (Jurnal Teknologi Perikanan dan Kelautan, 2025)
Banten Bay is a busy water area with diverse activities, including capture fisheries, aquaculture, marine and land transportation, and industry, which are estimated to generate significant amounts of heavy metals that enter the water and accumulate in fish and shellfish. Some fishery commodities commonly found in Banten Bay included shellfish, such as blood cockles, green mussels, mud crabs, and blue swimming crabs. The study aims to monitor heavy metal contamination variations spatially and temporally of the shellfish in Banten Bay. Biota samples were taken for 6 months in Cengkok Coastal Waters (March–August 2019) and 3 months in Bojonegara Coastal Waters (August–October 2020). The heavy metal content was determined using an atomic absorption spectrophotometer (AAS). Pb and Cd concentrations in the flesh of the shellfish (blood cockles, green mussels, mud crabs, and blue swimming crabs) from the Cengkok and Bojonegara Coastal Waters ranged from 0.001 to 0.070 ppm and from <0.001 to 0.030 ppm, respectively. All measured heavy metal concentrations met the BPOM (2018) quality standards. Bioconcentration factors were generally <100, indicating low accumulation levels.  Blood cockles, green mussels, and mud crabs from Cengkok Coastal Waters were still safe for consumption in normal amounts, while the consumption of swimming crabs was strictly limited to 0.42 kg/week for adults and 0.11 kg/week for children. The same four species from the Bojonegara Coastal Waters were also considered safe for consumption in normal portions.